On the electronic origins of structural isomerism in the iron-sulfur cubane, [(C(5)H(5))(4)Fe(4)S(4)](2+). - Knottenbelt, S; McGrady, J (2003)
Density functional theory provides new insights into the structural isomerism observed in the cyclopentadienyl-capped iron-sulfur cluster, [(C(5)H(5))(4)Fe(4)S(4)](2+). Two distinct, closely spaced minima have been located, a triplet with D(2) symmetry and a C(2)-symmetric singlet, both of which correspond closely to the structure of one of the known crystal forms of the cation. Thus, the structural diversity in these species reflects genuine molecular bistability rather than simple solid-state packing effects. In contrast, no stable D(2)(d)()-symmetric minimum has been located, suggesting that the reported D(2)(d)() symmetry of the cation in [(C(5)H(5))(4)Fe(4)S(4)][PF(6)](2) may be a crystallographic artifact. In the ruthenium analogue, the more diffuse 4d orbitals stabilize the C(2)-symmetric singlet, which is unambiguously the ground state, but the D(2)-symmetric potential energy surface provides a viable low-energy pathway for the dynamic exchange of the Ru-Ru bonds.